Standard Waiting Time for Hospital Discharge of Inpatients: Literatur Riview - Noviantoro, Alfajari; Sarwadhamana, Raden Jaka; Putri, Chera An Nisa; Hafidah, Diah Ayuni Nur; Nugraha, Faizqinthar Bima; Freeza, Fristi Nadila Mutiara; Khasanah, Lusi Alfi; Pratama, Muhammad Arinja Danu; Hayatusyifa, Rafika Putri; Apriani, Sindi; Nirmala, Traya (PROMOTOR, 2025)
Waiting time for inpatient discharge is the time from the time the patient is discharged by the doctor until the patient leaves the treatment room. The standard of waiting time for patient discharge has been set in the minimum service standard in Permenkes RI no 129 of 2008 where the waiting time for patient discharge does not exceed 2 hours (Depkes RI, 2008). The study aims to determine the waiting time for discharge of hospitalized patients in the hospital. This type of research is a literature review with the PICOST method in analyzing the problem and the process of searching for research articles. The literature approach also uses the PRISMA method which is carried out in an organized manner by complying with proper and consistent procedures and steps. The article search for 2019-2023 was carried out with the online database feature which found 213 journal articles collected from Science Direct, PubMed and Google Scholar and selected 5 articles that met the inclusion criteria for review. The results showed that the average waiting time for hospital discharge was 3.4 hours.